Communication studies cartography in the Lusophone world - Martins, Moisés de Lemos (2018)
Within the Lusophone community of over 250 million speakers only a minority developed a sense of belonging based on their common language, a phenomenon that is still very real today. According to the Mozambican writer, Mia Couto, Lusophony is not a ‘loud’ reality, rather a “luso-aphonic” one, that is, a place of low voices, no knowledge and no acknowledgement of the commonalities between themselves in this vast geographic and cultural space. Recognizing precisely this gap, Communication research associations in Lusophone countries (Lusocom) have promoted the setting up of a research cooperation network primarily between Portuguese and Brazilian researchers, and then extending it to the Galician community, and subsequently to the entire Lusophone space. This movement is based on the assumption that linguistic diversity enriches science and that science should be globally and contextually relevant. Lusophony can be discussed from various points of view, all related to the cultural identity of the Portuguese-speaking countries. I would like to explain my point of view, focused on the social status of language. Then, I will refer to the English language has a dominant language. Finally, I would like to point out some challenges that, from my perspective, the Lusophone research groups have to face in a global world dominated by English and anglo-saxon paradigms. My approach is in fact focused on the perspective of language, understood as a cultural manifestation, the expression of thought, a relational space, and an instrument of symbolic organization of the world. Such understanding is coincident with the symbolic power of language (Pierre Bourdieu’s theory), and with the post-colonial perspective which questions the domination, submission, subordination and control of peripheries, minorities, diasporas, migrants…